On the ethical-aesthetic potentials of special atmospheres (Lebenswelt. Aesthetics and philosophy of experience., 2014)
Discussions concerning the atmospheric raise questions about how it can be defined and what influences may stem from particular atmospheres. Moreover, a shift in emphasis can be seen in respect of the way phenomena and disciplines are understood. Aesthetics is considered to be a theory of sensual perception; ethics serves as a theory of the good life. The article focuses on the relationship between atmospheres and aesthetics (e.g. Benjamin’s ‘aura’ and Rilke on Rodin’s sculptures) as well as atmospheres and ethics (e.g. architecture or politics as façade) and concludes with three points about ethical-aesthetic potentials, thus enhancing in-betweenness, the development of aesthetic interest, as well as a re-evaluation.